The Role Of Women In Driving Inclusive Economic Growth - Dr. M. Surath Sheba; Dr. D. Thanaseeli (Revista Electronica de Veterinaria, 2024)
Women play a pivotal role in fostering inclusive economic growth by contributing to labor markets, entrepreneurship, and decision-making. However, gender disparities in education, wages, and access to resources hinder their full potential. This study explores the contribution of women to economic growth and identifies barriers preventing equitable participation. Through a mixed-method approach, the paper highlights key sectors where women’s involvement has the highest impact and provides actionable recommendations to bridge gender gaps in economic opportunities